Diplomatic relations of Cuba and United States - Voiles, Alberta Suena (My University, 1903)
Introduction: The Diplomatic Relations of Cuba and the United States. In the beginning of our study concerning the relations of Cuba and the United States, let us first take a brief review of the relations of Spain and the United States. Spain had acquired a great amount of territory in the Western Continent; at least one half of this continent was owned by her. In 1800 she ceded Louisiana to France. This was the first of her losses, the rest follow, on after another until no Spanish possessions remained in the new World except Cuba and Porto Rico. It was Cuba which caused the years of trouble between Spain and the United States. During these years Spain was constantly growing weaker while the United States was increasing in strength and becoming one of the greatest nations in the world. Three times before the war of 1898 Spain and the United States were at swords points: (1) during Jefferson’s administration, (2) in 1854, when the Black Warriors was fired upon and (3) in 1873 when Virginians was captured and some on board were executed. Cuba, situated as it is at the mouth of the gulf, seemed destined to fall into the hands of the United States. If this island were held by an enemy our western commerce could easily be blockaded. Cuba had patiently borne the injustices Spain had inflicted upon it during the years of Spanish Government. They had been very severely oppressed and taxed. In 1812 a somewhat consistent constitution was originated for Cuba but it was never put into effect.
Citation: Voiles, Alberta Suena. Diplomatic relations of Cuba and United States. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Diplomatic relations; Cuba; United States; Theses